Entre a teoria e a prática da mediação cultural: apontamentos a partir do FACTORS 8.0 - Quaiatto, Rittieli (Farol, 2023)
In this article, I address the cultural mediation project developed during the eighth edition of the Festival of Art, Science, and Technology - FACTORS 8.0, which took place in 2021 on Instagram and YouTube. My aim is to stimulate a critical reflection on the mediation strategies employed in art exhibitions, particularly in online showcases, during the period of social isolation resulting from the pandemic. To achieve this, I draw upon the realms of Art and Cultural Mediation as a theoretical foundation, and expound upon my involvement with the festival's educational team, analyzing the project's implementation and discussing the observed gap between the team's expectations and the reality of proposal execution. Finally, I emphasize the need for the creation of specific metrics to assess project reach, genuine engagement, and audience experience in these events.
Keywords: Cultural Mediation. Art and Technology. Virtual Exhibition. Audiences. Pandemic.